Application of Protocol Buffer in Enterprise Cloud Contacts Abstract This paper introduces the method to use Protocol Buffer to update data in enterprise cloud contacts, and compares the time and size of XML（extensible markup language）, JSON（JavaScript object notation）and Protocol Buffer, through the test data. - Hao Yin; Qiwei Shen; Chun Wang (Dianxin kexue)
This paper introduces the method to use Protocol Buffer to update data in enterprise cloud contacts, and compares the time and size of XML（extensible markup language）, JSON（JavaScript object notation）and Protocol Buffer, through the test data.